Structural evolution of mechanical heart valves (review) - M. A. Lepilin; A. V. Bogachev-Prokophiev; М. О. Zhulkov; D. S. Khvan; D. A. Sirota; A. G. Makaev; A. V. Protopopov; A. S. Grenadyorov; Kh. A. Agaeva; A. М. Chernyavskiy (Вестник трансплантологии и искусственных органов)
Prosthetic heart valves are widely used biomedical devices. The need for these prostheses is increasing due to the increasing life expectancy of the general population and the consequent incidence of age-related degenerative valvular defects. However, even though mechanical prosthetic valves have been significantly modernized over the last decades, they are still associated with several life-threatening complications, the main one being thrombosis. Addressing this problem is challenging and requires collaboration between bioengineering and cardiothoracic surgery. Thus, the problem of creating the most adapted model of prosthetic heart valve (PHV) turns out to be at the confluence of sciences – medicine, biology, applied mechanics, mathematical modeling, etc. Today, it seems clear that the engineering ideas for hemodynamic adaptation of PHV models have been fully developed. However, research in the field of materials science, as well as a search for surface modification methods, remain a pressing bioengineering challenge.